APLIKASI MACAM PUPUK ORGANIK (VERMIKOMPOS, ECENG GONDOK, PUPUK KANDANG) DAN MACAM PUPUK P (TSP, ROCK PHOSPATE, SP36) TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY - Ramadhan, Agung Fadillah; Syah, Ryan Firman; Kristalisasi, Elisabeth Nanik (Institute of Computer Science (IOCS), 2025)
Palm oil is a commodity of plantation plantations that produce vegetable oils that are very instrumental in various industries. To increase good production of palm oil must be maintained. Actions are carried out from planting to the end of the harvest. Fertilization is in the form of its actions. This lesson wants to explore each contribution from the aspects that have been determined to be the core of the problem topic that we want to raise. The lesson was held in the designated community area from October 2024- January 2025. The lesson was through a designed trial (RAL) from some aspects. The initial aspect of the type of organic fertilizer which includes 4 levels: Vermicompost, Control, Water Hyacinth Compost & Cow Manure. From the second aspect of P fertilizer which includes some: SP36, Rock Phosphate & TSP. Then 12 combined actions were found from the 4 x 12 = 48 plant trials. This lesson shows that there is no real relationship between P and Organic actions on Seedling Development. Water hyacinth compost given 250g/polybag contributes to the stem and height of the seedlings. Giving P at a dose of 1.5g/polybag contributes to the development of early nursery sekeywords are goodedlings.